2018
DOI: 10.1016/j.idcr.2018.03.003
|View full text |Cite
|
Sign up to set email alerts
|

A case of acute disseminated encephalomyelitis following Mycoplasma pneumoniae infection

Abstract: We report a case of acute disseminated encephalomyelitis (ADEM) secondary to Mycoplasma pneumoniae infection that failed to improve with methylprednisolone and intravenous immunoglobulin (IVIG); who responded with plasmapheresis. A 21- year- old female with an unremarkable medical history, initially presented to an outside hospital with fever and an influenza-like illness and was subsequently intubated for worsening sensorium. Brain magnetic resonance imaging was suggestive of ADEM or vasculitis for which she … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…It should be in the differential diagnosis whenever respiratory symptoms are followed by neurological manifestations and encephalopathic signs (24). Brain MRI is extremely useful to establish a diagnosis of ADEM; with better visualization of the demyelinating lesions (25). In this study, one patient developed ADEM with abnormal brain MRI and occurred serious sequelae.…”
Section: Discussionmentioning
confidence: 66%
“…It should be in the differential diagnosis whenever respiratory symptoms are followed by neurological manifestations and encephalopathic signs (24). Brain MRI is extremely useful to establish a diagnosis of ADEM; with better visualization of the demyelinating lesions (25). In this study, one patient developed ADEM with abnormal brain MRI and occurred serious sequelae.…”
Section: Discussionmentioning
confidence: 66%
“…2,3 There are few reports worldwide in the English literature of ADEM due to M pneumoniae infection; 19 including a report in a young adult from UAE. 20 Al-Zaidy Sa, et al 21 reported ADEM in 12% of those patients whom had neurologic disease attributable to M pneumoniae infection. 21 The underlying mechanism for the CNS complications include either direct invasion into the CSF or a systemic immune-mediated response provoked by molecular mimicry 2 to 3 weeks after the respiratory disease subsided.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few described cases have been associated with CMV and none of them, to the best of our knowledge, in an immunocompromised patient. ADEM associated with systemic lupus erythematosus (SLE) has rarely been reported [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%